THE DEVELOPMENT STRATEGY OF INTERNATIONAL COMPANIES IN MODERN CONDITIONS - Djurabayev Otabek Djurabayevich; Khanbekova Alina Timurovna (TADQIQOTLAR.UZ, 2024)
Abstract. This article develops strategies for the development of international companies in modern conditions; the basic concepts of the development strategy of international companies in modern conditions are revealed; analyzed the activities of the association "Uztekstilprom"; practical proposals have been developed to improve the development strategy of the association "Uztekstilprom"